Letter from Carl Duncan to Patricia Whiting, September 11, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan welcomes Whiting back from her trip to Mexico and recalls the events of his week, including Freshman camp and a visit to Point Lobos.